2008
DOI: 10.1152/ajpregu.00874.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-specific responses of muscle glycogen repletion in fasted rats physically active during recovery from high-intensity physical exertion

Abstract: Mild physical activity performed immediately after a bout of intense exercise in fasting humans results in net glycogen breakdown in their slow oxidative (SO) muscle fibers and glycogen repletion in their fast twitch (FT) fibers. Because several animal species carry a low proportion of SO fibers, it is unclear whether they can also replenish glycogen in their FT fibers under these conditions. Given that most skeletal muscles in rats are poor in SO fibers (<5%), this issue was examined using groups of 24-h fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
(75 reference statements)
0
1
2
2
Order By: Relevance
“…In addition, the composition of muscle fibers is closely correlated with glycogen stores and fast-twitch fibers are abundant in glycogen content. 50 However, the regulatory effects of YPLP on fasttwitch fibers in vitro were not positively correlated with the regulatory effects on glycogen content in vivo in the current study. This is probably because the composition of skeletal muscle fibers is various in different parts of the muscle tissue in vivo.…”
Section: ■ Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In addition, the composition of muscle fibers is closely correlated with glycogen stores and fast-twitch fibers are abundant in glycogen content. 50 However, the regulatory effects of YPLP on fasttwitch fibers in vitro were not positively correlated with the regulatory effects on glycogen content in vivo in the current study. This is probably because the composition of skeletal muscle fibers is various in different parts of the muscle tissue in vivo.…”
Section: ■ Discussioncontrasting
confidence: 80%
“…Calbet and MacLean reported that active peptides could also stimulate the secretion of insulin, promoting the generation of glycogen. In addition, the composition of muscle fibers is closely correlated with glycogen stores and fast-twitch fibers are abundant in glycogen content . However, the regulatory effects of YPLP on fast-twitch fibers in vitro were not positively correlated with the regulatory effects on glycogen content in vivo in the current study.…”
Section: Discussioncontrasting
confidence: 70%
“…One determinant of GS activity is the existing amount of glycogen within the muscle as well as muscle fiber type [77,78]. As demonstrated in rodents, low glycogen content was associated with decrease in GS phosphorylation and high glycogen content was associated with decrease in GS activation [79][80][81].…”
Section: Perspectivesmentioning
confidence: 95%
“…Conforme relatado anteriormente, os estoques de glicogênio muscular desempenham papel importante no aporte energético durante uma sessão aguda de exercício de alta intensidade (Raja et al, 2008). Sendo assim, a recuperação dos estoques depletados durante um exercício ocorre, sobre condições favoráveis, preferencialmente em fibras de contração rápida (Raja et al, 2008).…”
Section: Sessões Agudas De Exercício Dinâmica De Recuperação E Metabo...unclassified
“…Conforme relatado anteriormente, os estoques de glicogênio muscular desempenham papel importante no aporte energético durante uma sessão aguda de exercício de alta intensidade (Raja et al, 2008). Sendo assim, a recuperação dos estoques depletados durante um exercício ocorre, sobre condições favoráveis, preferencialmente em fibras de contração rápida (Raja et al, 2008). E, como mostrado por Sano et al (2012) uma sessão aguda de natação de alta intensidade e curta duração (8 x 20 segundos; 18% do peso corporal), em condições favoráveis de consumo de carboidrato, causa a supercompensação do glicogênio de forma similar ao que ocorre com um exercício de alto volume (3 horas sem carga adicional).…”
Section: Sessões Agudas De Exercício Dinâmica De Recuperação E Metabo...unclassified